Fungi and bacteria of Meloidogyne paranaensis egg masses from coffee crops are toxic to Meloidogyne incógnita - López, Liliana Estupiñan (2017)
Meloidogyne species produce egg masses containing nutrients which may serve as feeding substrate for rhizospheric microorganisms. In the present work we isolated fungi and bacteria form Meloidogyne paranaensis egg masses. Amongst the fungi isolated 67% belonged to the Fusarium genus and within those 52% of the isolates were of the F. oxysporum species and were found seven different genera of bacteria, predominating Pseudomonas genus. Isolates from F. oxysporum and F. solani causing up to 100% immobility in in vitro tests and reduced M. incognita infectivity and reproduction in tomato when J2 were exposed to fungal volatiles. Also, bacteria isolates reducing 99% infectivity and reproduction when exposed to bacterial vapors, compared to the control. Water exposed to vapors by fungi and bacteria and mixed to the J2 suspension caused toxicity in M. incognita J2 and reduced infectivity and reproduction of nematodes inoculated in tomato, when compared to the control. Using gas chromatography-mass spectrometry technique (GC-MS), the volatile compounds produced by fungi and bacteria were identified and gathered in 8 main categories: esters, alcohols, phenols, aldehydes, ketones, carboxylic acids, sulfur compounds and sesquiterpenes. For the first time, molecules from various chemical groups were identified in the water exposed to the volatiles from fungi and bacteria isolates. Within these molecules, various have been already reported as having high nematicidal activity, therefore, fungi and bacteria from M. paranaensis egg masses, produce volatile compounds with antagonistic activity to M. incognita.